1995
DOI: 10.1139/m95-093
|View full text |Cite
|
Sign up to set email alerts
|

ThentrBCgenes ofAzospirillum brasilenseare part of anifR3-like–ntrBntrCoperon and are negatively regulated

Abstract: A cosmid able to complement the Nif- and nitrate-dependent growth phenotypes of the Azospirillum brasilense mutant FP9 was isolated from a genomic library of the wild-type strain FP2. A 6-kb DNA region was sequenced and showed two open reading frames (ORFs) identified as the ntrB and ntrC genes. An ORF1 located upstream from the ntrB gene and coding for a 36-kDa polypeptide showed similarity to the nifR3 gene of Rhodobacter capsulatus and the ORF1 of Rhizobium leguminosarum, both located upstream from the ntrB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 29 publications
2
33
0
1
Order By: Relevance
“…The hybridization results (data not shown) showed that the Km cassette was inserted into the chromosome of these mutants, however, at a site different from the ntrY gene. These results were surprising since this method of mutagenesis had previously yielded ntrBC mutants of A. brasilense (15). The reasons for our failure to obtain A. brasilense ntrY or ntrX mutants are not known.…”
Section: Attempts To Construct Ntry Mutants Of a Brasilensementioning
confidence: 84%
See 4 more Smart Citations
“…The hybridization results (data not shown) showed that the Km cassette was inserted into the chromosome of these mutants, however, at a site different from the ntrY gene. These results were surprising since this method of mutagenesis had previously yielded ntrBC mutants of A. brasilense (15). The reasons for our failure to obtain A. brasilense ntrY or ntrX mutants are not known.…”
Section: Attempts To Construct Ntry Mutants Of a Brasilensementioning
confidence: 84%
“…Identification and sequencing of the ntrYX genes The 4.85-kb insert of plasmid pSPL46 was fully sequenced and showed the pres- (Figure 2), determined according to Kyte and Doolittle (30), revealed four hydrophobic regions in the Nterminus equivalent to the putative transmembrane regions of A. caulinodans NtrY (1), and to those of the E. coli and Salmonella typhimurium chemoreceptor proteins (15) sequenced the N-terminal region of NtrY downstream from the ntrC gene and reported constitutive promoter activity located in the intergenic region in an E. coli background. These results suggest that the ntrYX operon is expressed from its own promoter although readthrough from an upstream promoter cannot be ruled out due to the absence of a transcription terminator sequence downstream from the ntrC gene.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations